Effect of Pile-Soil Relative Stiffness on Deformation Characteristics of the Laterally Loaded Pile - Bingxiang Yuan; Minjie Chen; Weijie Chen; Qingzi Luo; Hongzhong Li (Advances in Materials Science and Engineering)
Laterally loaded piles are widely used in structural foundations under horizontal loads such as wave load, wind load, seismic load, and traffic load. Based on the complexity of pile-soil interaction, a test simulation of single pile through the indoor 1 g model test was conducted, in order to study the influence of different loading heights and relative stiffness of pile and soil on the bending moment, soil resistance, and horizontal displacement of pile. It is found that the shear modulus of soil from large to small is arranged as dry fine sand, dry coarse sand, saturated fine sand, and saturated coarse sand. The shear modulus of dry fine sand, dry coarse sand, and saturated fine sand are close under the same loading height and horizontal displacement of pile top, while the shear modulus of saturated coarse sand decreases sharply. Under the condition of water saturation, the particle size has a significant effect on the shear modulus of soil. The relative stiffness of pile soil is found to be the main influencing condition of pile horizontal displacement. Compared with the displacement and bending moment of the pile, the loading height has more influence on the soil resistance, and the main influence area is the soil resistance of the pile toe.